Conceptualizing the role of patient satisfaction in the relation between services quality and patient loyalty in Jordan public hospitals - Puspa Liza, Ghazali; Juliana, Arifin; Roslida, Abdul Razak; Salahaldeen, Alkawamleh; Eni Noreni, Mohamad Zain; Sukono, .; Rini, Cahyandari; Abdul Talib, Bon (2021)
The aim of this study to empirically validate of role of patient satisfaction in the relation between health services quality and staff performance and patient loyalty. A total of 357 patients from government hospitals in Jordan have needed to answer the questionnaires. The collect data will be analysed with Structure Equation Modelling (SEM). The proposed model that represents the study model in health procedures that dealing with patients will helps health managers and planners to improve the levels of treatment and health services in MOH hospitals in Jordan and the researcher recommends to conducts further studies to extend this model to health system.